Peran Teknologi Digital dalam Menyebarkan Dakwah Islam di Era Modern dalam Konten YouTube Studio Al-Fusha TV - Durrotul Fairuz; Nur Kholis Eka Safitri; Ahmad Hidayatullah (Mu'ashir: Jurnal Dakwah dan Komunikasi Islam, 2024)
This research examines the important role of digital technology, especially YouTube Studio Al-Fusha TV, in spreading Islamic da'wah in the modern era. Using qualitative methods with a case study approach, this research analyzes Al-Fusha TV content to understand the use of digital technology in da'wah. This research aims to explore the role of digital technology, especially the YouTube Studio Al-Fusha TV platform, in spreading Islamic da'wah in the modern era. The results show that YouTube Studio Al-Fusha TV is effective in spreading the message of Islamic da'wah to a wider audience, with diverse content such as interpretations of the Koran, hadith studies, and religious discussions.